EVOLUTION OF LEARNING SYSTEMS: FROM LEARNING MANAGEMENT SYSTEMS TO ADAPTIVE LEARNING SYSTEMS BASED ON ARTIFICIAL INTELLIGENCE - Bahrul Alam; Ahmad Kosim; Eny Ermawaty; Sarwiyanti (Multidiciplinary Output Research For Actual and International Issue (MORFAI), 2025)
Digital transformation in education has driven a paradigm shift from the use of Learning Management Systems (LMS) to the development of Adaptive Learning Systems (ALS) based on artificial intelligence (AI). This article aims to examine the evolution of this learning system through a literature study approach to 16 national and international scientific articles in the 2015–2025 period. The results of the study indicate that the integration of AI in the learning system strengthens personalization, student engagement, and the effectiveness of learning achievement. LMS has now evolved from a managerial and content distribution platform into an ALS that is adaptive and responsive to the characteristics of individual learners. However, this transition process is not without challenges, including the need for representative data training, the readiness of technological infrastructure, and issues of data ethics and privacy. This study recommends an integrative and inclusive strategy in the implementation of AI-based ALS to realize a dynamic, personal, and sustainable digital learning ecosystem.